The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.12.29.474467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of critical genes and biological signaling for metformin treated liver cancer

Abstract: Liver cancer is a leading source of cancer-related mortality in the world. A number of studies have shown the correlation of metformin treatment with a decrease in cancer risk. However, the relevant molecules and mechanisms are not clear during the treatment. In this study, our aim is to identify the significant molecules and signaling pathways in the treatment of metformin in liver cancer cells by analyzing the RNA sequence. The GSE190076 dataset was created by performing the Illumina NovaSeq 6000 (Homo sapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…ZWINT is a crucial constituent of the mitotic spindle checkpoint, which plays a pivotal role in ensuring accurate chromosome segregation during cell division and maintaining genomic stability. [14,15] Recent studies have shown that ZWINT may be involved in the pathogenesis of tumour development and is overexpressed in a variety of malignancies including colon, breast, liver, lung and pancreatic cancers [8,[16][17][18][19][20][21] .However, the regulation of ZWINT in ovarian cancer and its molecular mechanism have not been reported yet. The results of this study showed that ZWINT was significantly highly expressed in ovarian cancer tissues, the higher the expression level of ZWINT, the worse the overall survival and disease-free survival of the patients, which indicates that ZWINT is closely related to the development of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ZWINT is a crucial constituent of the mitotic spindle checkpoint, which plays a pivotal role in ensuring accurate chromosome segregation during cell division and maintaining genomic stability. [14,15] Recent studies have shown that ZWINT may be involved in the pathogenesis of tumour development and is overexpressed in a variety of malignancies including colon, breast, liver, lung and pancreatic cancers [8,[16][17][18][19][20][21] .However, the regulation of ZWINT in ovarian cancer and its molecular mechanism have not been reported yet. The results of this study showed that ZWINT was significantly highly expressed in ovarian cancer tissues, the higher the expression level of ZWINT, the worse the overall survival and disease-free survival of the patients, which indicates that ZWINT is closely related to the development of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%